Karakteristik Bioplastik Pati Bonggol Pisang Dengan Variasi Konsentrasi Gliserol - Putra, Endo Pebri Dani; Larassati, Dyah Putri; Wijayani, Rizky Aden; Thamrin, Elfa Susanti; Sylvia, Teny; Subara, Deni; Laksono, Untung Trimo (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Plastic packaging is extensively utilized in contemporary society. The non-biodegradable nature of plastic poses significant environmental challenges; consequently, an alternative solution, namely bioplastic, is necessitated. Bioplastics are environmentally sustainable polymers that readily decompose in natural environments through microbial action. Banana weevil starch serves as a primary component in bioplastic production. Glycerol, an additional constituent in bioplastics, functions as a plasticizer to enhance the elasticity of the resultant bioplastics. This study aims to analyze the effect of glycerol concentration variations on the characteristics of banana hump starch bioplastic and determine the optimal glycerol concentration for achieving desired bioplastic properties. The research methodology employed a Completely Randomized Design (CRD) with five variables, specifically glycerol concentrations of 1%, 2%, 3%, 4%, and 5%. The evaluation of bioplastic characteristics encompassed thickness, density, water absorption, tensile strength, elongation, Young's modulus, and biodegradation of bioplastics. The research findings indicate that the most favorable bioplastic characteristics were observed at a glycerol concentration of 1%, with a thickness of 0.106 mm + 0.006, density of 1.534 g/cm3 + 0.065, water absorption capacity of 58.682% + 0.075, tensile strength of 16.490 MPa + 2.497, elongation of 14.413%, Young's modulus of 121.362 MPa + 34.505, and degradation percentage of 12.992% + 0.012.